Predictors of returning home after hip fracture: a prospective cohort study using the UK National Hip Fracture Database (NHFD). (2nd August 2022) - Hawley, Samuel; Inman, Dominic; Gregson, Celia L; Whitehouse, Michael; Johansen, Antony; Judge, Andrew
Abstract: Introduction: our objective was to describe trends in returning home after hospitalisation for hip fracture and identify predictive factors of this important patient-focussed outcome. Methods: a cohort of hip fracture patients from England and Wales (2018–2019) resident in their own home pre-admission were analysed to identify patient and service factors associated with returning home after hospital discharge, and with living in their own home at 120 days. Geographical variation was also analysed. Results: analysis of returning home at discharge included 87, 797 patients; 57, 104 (65%) were discharged home. Patient factors associated with lower likelihood of discharge home included cognitive impairment (odds ratio (OR) 0.60 [95% CI: 0.57, 0.62]), malnutrition (OR 0.81 [0.76, 0.86]), being at risk of malnutrition (OR 0.81 [0.78, 0.85]) and experiencing delay to surgery due to reversal of anti-coagulant medication (OR 0.84 [0.77, 0.92]). Corresponding service factors included surgery delay due to hospital logistical reasons (OR 0.91 [0.87, 0.95]) and early morning admission between 4:00 and 7:59 am (OR 0.83 [0.78, 0.89]). Nerve block prior to arrival at the operating theatre was associated with higher likelihood of discharge home (OR 1.07 [1.03, 1.11]). Most of these associations were stronger when analysing the outcome 'living in their own home at 120 days', in which two out of 11 geographic regions were found to have significantly more patients returning home. Conclusion: we identify numerous modifiable factors associated with short-term and medium-term return to own home after hip fracture, in addition to significant geographical variation. These findings should support improvements to care and inform future research.